2009
DOI: 10.2108/zsj.26.765
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Analysis of the Japanese Wolf (Canis Lupus HodophilaxTemminck, 1839) and Comparison with Representative Wolf and Domestic Dog Haplotypes

Abstract: Mitochondrial DNA (mtDNA) D-loop control region sequences ranging In length from 583 to 598 bp were determined for eight Japanese wolf specimens (Canis lupus hodophilax Temminck, 1839) collected from several sites and compared with 105 haplotypes from the domestic dog (C. lupus familiaris) and continental grey wolf (C. lupus lupus). Also, a 197-bp mtDNA sequence was amplified from archaeological wolf specimens and two continental wolf specimens (C. lupus chanco) as reference sequences for analysis. The mtDNA h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 11 publications
6
26
0
Order By: Relevance
“…11 According toObara (2002), the skull is from a domestic dog. This is in line withObara and Nakamura (1992) where the skull of a Yamainu was identified as belonging to a native feral dog (Canis familiaris); see also the discussion byIshiguro et al (2009).12 The skin has well-developed dugs.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…11 According toObara (2002), the skull is from a domestic dog. This is in line withObara and Nakamura (1992) where the skull of a Yamainu was identified as belonging to a native feral dog (Canis familiaris); see also the discussion byIshiguro et al (2009).12 The skin has well-developed dugs.…”
supporting
confidence: 83%
“…Wozencraft (2005: 576) included Canis hodophilax Temminck, 1839 as a synonym of Canis lupus. However, many zoologists classify the extinct Japanese wolf as Canis lupus hodophilax (Miyamoto and Maki 1983) and this is supported by Ishiguro et al (2009) following an analysis of mitochondrial DNA from eight specimens of the Japanese wolf compared to the DNA of domestic dogs and continental Canis lupus.…”
Section: Unravelling the Lectotype And Conclusionmentioning
confidence: 99%
“…However, haplotypes deriving from crossbreeding would normally have limited geographical spread unless a superior phenotype would have evolved (Pang et al , 2009; Klütsch et al , 2010), and may have gone undetected in this study. So far, the only clear genetic evidence of wolf–dog crossbreeding is the regionally restricted mtDNA haplogroups d1 (restricted to Scandinavia), d2 (restricted to the Middle East and the Mediterranean), and F (found only in a few extant Japanese dogs and samples from extinct Japanese wolf) (Ishiguro et al , 2009; Pang et al , 2009; Klütsch et al , 2010). …”
Section: Discussionmentioning
confidence: 99%
“…For example, two distinct mtDNA lineages were discovered in India and Himalaya [3]–[5] that are basal to other grey wolf lineages worldwide. Another distinct lineage was discovered in Japan [6]. Studies on morphological diversity also identified a variety of distinct types of grey wolves in Asia, which constituted a basis for subspecies delimitation (see [7] for review).…”
Section: Introductionmentioning
confidence: 99%